Adding a temporal dimension to the analysis of argumentative discourse: Justified reframing as a means of turning a single-issue discussion into a complex argumentative discussion. (December 2018) - Greco, Sara; Schär, Rebecca; Pollaroli, Chiara; Mercuri, Chiara
This article seeks to extend existing models of argumentation by considering an important dimension of real-life argumentative discourse: how complex argumentative discussions evolve over time. We define a complex argumentative discussion as a multi-issue discussion, in which the different issues are interrelated in the form of a hierarchy. We claim that justified reframing might be used to transform a single-issue argumentative discussion into a complex argumentative discussion. To illustrate this, we examine the Facebook discourse of the Rhodes Must Fall movement in South Africa. We analyse how reframing is justified by means of arguments, allowing the protagonists to claim as legitimate their reframing of a single issue into a complex argumentative discussion. Our findings complement existing sociological research on social movements by highlighting how their goals are achieved by means of argumentative discourse.